Extending the Frontiers of Electronic Commerce Knowledge through Cybersecurity - Vuță Daniela Roxana; Nichifor Eliza; Țierean Ovidiu Mircea; Zamfirache Alexandra; Chițu Ioana Bianca; Foris Tiberiu; Brătucu Gabriel (Electronics, 2022)
As technology becomes more sophisticated so do cyber-attacks. The resilience of electronic commerce organisations represents a critical point nowadays because it influences consumer and digital business behaviour. In this context, the cybersecurity and electronic commerce knowledge were reviewed as a unit. The main aim of this paper is to support researchers and managers in understanding the theoretical framework and to provide a knowledge-based model. To achieve this aim, the authors performed an analysis of 14,585 papers from the Web of Science Core Collection that generated two visualized networks, analyzed with the metrics mean silhouette, modularity, betweenness centrality, and citation bursts in the context of digital resilience. The mapping process results show that the human factor represents the central junction with the fear of cyber-attacks and the perception of online shopping as risky. The adoption of electronic commerce and mobile commerce are two challenging research lines in the global economic resilience. Their adoption enabled by big data, artificial intelligence, machine learning, and even blockchain technology can strengthen resilience even when cybersecurity education is needed.
This article was originally published in Electronics (MDPI) and is licensed under a Creative Commons Attribution (CC BY) 4.0 International License. This license permits use, sharing, distribution, and reproduction in any medium or format, provided proper credit is given to the original authors and source, a link to the license is included, and any changes made are indicated. The article is available at: https://www.mdpi.com/2079-9292/11/14/2223 To view a copy of this license, visit: http://creativecommons.org/licenses/by/4.0/